2007 18th International Zurich Symposium on Electromagnetic Compatibility 2007
DOI: 10.1109/emczur.2007.4388226
|View full text |Cite
|
Sign up to set email alerts
|

MoM based EMI analysis on large wind turbine GSM 900 MHz communication backup-system

Abstract: Electro-magnetic fields resulting from a GSM transmitter mounted on a large wind turbine will be analyzed. This cellular system operates as novel communication backup in case the standard communication between operator and hub control systems is interrupted. The method-of-moments is used to analytically describe the electro-magnetic fields caused by a GSM 900 MHz transmitter mounted on the hub of a wind turbine. Using a commercial simulation tool the electromagnetic field distribution will be analyzed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Also, there have been some studies concentrated on the performance degradation/deterioration assessment of electronic systems because of different EM interaction phenomena, for example, line‐of‐sight (LOS), Fresnel zone and shadowing [7, 11]. It has been shown that the presence of WTs can cause degradations on electronics systems’ performances depending on near‐ and far‐field scattering effects [5, 11–14]. The effects of the Doppler shift caused by the rotating blades of the WTs have also been investigated [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…Also, there have been some studies concentrated on the performance degradation/deterioration assessment of electronic systems because of different EM interaction phenomena, for example, line‐of‐sight (LOS), Fresnel zone and shadowing [7, 11]. It has been shown that the presence of WTs can cause degradations on electronics systems’ performances depending on near‐ and far‐field scattering effects [5, 11–14]. The effects of the Doppler shift caused by the rotating blades of the WTs have also been investigated [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…(i) Scattered field: to implement this kind of analysis, both high-and-low frequency techniques, such as GTD/UTD and MoM, respectively, have been used. Nevertheless, due to the tremendous size of this kind of structure [11][12][13][14], the application of MoM is limited only to low frequencies. Thus, PO and an hybridized MoM-PO approximation have been used to perform simulations of huge structures at high frequencies.…”
Section: Introductionmentioning
confidence: 99%